Sexuality and obesity, a gender perspective: results from French national random probability survey of sexual behaviours. (15th June 2010) - Bajos, Nathalie; Wellings, Kaye; Laborde, Caroline; Moreau, Caroline
Abstract : Objectives To analyse the association between body mass index (BMI) and sexual activity, sexual satisfaction, unintended pregnancies, and abortions in obese people and to discuss the implications for public health practices, taking into account the respondents' and their partners' BMI. Design Random probability survey of sexual behaviours. Setting National population based survey of 12 364 men and women aged 18-69 living in France in 2006. Participants Random selection of 5535 women and 4635 men, of whom 3651 women and 2725 men were normal weight (BMI 18.5-<25), 1010 women and 1488 men were overweight (BMI 25-<30), and 411 women and 350 men were obese (BMI >30). Results Obese women were less likely than normal weight women to report having a sexual partner in the past 12 months (odds ratio 0.71, 95% confidence interval 0.51 to 0.97). Obese men were less likely than normal weight men to report more than one sexual partner in the same period (0.31, 0.17 to 0.57, P<0.001) and more likely to report erectile dysfunction (2.58, 1.09 to 6.11, P<0.05). Sexual dysfunction was not associated with BMI among women. Obese women aged under 30 were less likely to seek healthcare services for contraception (0.37, 0.18 to 0.76) or to use oral contraceptives (0.34, 0.15 to 0.78). They were also more likely to report an unintended pregnancy (4.26, 2.21 to 8.23). Conclusion There is a link between BMI and sexual behaviour and adverse sexual health outcomes, with obese women less likely to access contraceptive healthcare services and having more unplanned pregnancies. Prevention of unintended pregnancies among these women is a major reproductive health challenge. Healthcare professionals need to be aware of sensitivities related to weight and gender in the provision of sexual health services.